Pengaruh Kepemimpinan Transformasional dan Transaksional serta Motivasi Kerja Terhadap Kinerja dan Kepuasan Individual Karyawan dalam Organisasi Perusahaan Industri Telekomunikasi - Komardi, Didi (Universitas Brawijaya, Indonesia, 2009)
This study is held in attempt to observe and present how far influence of leadership that assumed can meet high performance as well as control competition level and strong challenge namely Transformational and Transactional Leadership as well as work motivation through performance and employee satisfaction on implementation structure in organization that has globalization market, fast development and high competition. The result study shows that : (1) Transformational leadership can provide significant influence and positive through work motivation, (2) while transformational relevant leadership with performance has non significant influence, (3) Transactional leadership through work motivation and individual can influence individual performance, (4) work motivation can influence work individually, as well as (5) employee performance relationship with satisfaction have significant influence and positive.